Ulcerative skin lesions among children in Cameroon: It is not always Yaws. - Jean-Philippe Ndzomo Ngono; Serges Tchatchouang; Mireille Victorine Noah Tsanga; Earnest Njih Tabah; Albert Tchualeu; Kingsley Asiedu; Lorenzo Giacani; Sara Eyangoh; Tania Crucitti (PLoS Neglected Tropical Diseases)
Outbreaks of yaws-like ulcerative skin lesions in children are frequently reported in tropical and sub-tropical countries. The origin of these lesions might be primarily traumatic or infectious; in the latter case, Treponema pallidum subspecies pertenue, the yaws agent, and Haemophilus ducreyi, the agent of chancroid, are two of the pathogens commonly associated with the aetiology of skin ulcers. In this work, we investigated the presence of T. p. pertenue and H. ducreyi DNA in skin ulcers in children living in yaws-endemic regions in Cameroon. Skin lesion swabs were collected from children presenting with yaws-suspected skin lesions during three outbreaks, two of which occurred in 2017 and one in 2019. DNA extracted from the swabs was used to amplify three target genes: the human β2-microglobulin gene to confirm proper sample collection and DNA extraction, the polA gene, highly conserved among all subspecies of T. pallidum, and the hddA gene of H. ducreyi. A fourth target, the tprL gene was used to differentiate T. p. pertenue from the other agents of human treponematoses in polA-positive samples. A total of 112 samples were analysed in this study. One sample, negative for β2-microglobulin, was excluded from further analysis. T. p. pertenue was only detected in the samples collected during the first 2017 outbreak (12/74, 16.2%). In contrast, H. ducreyi DNA could be amplified from samples from all three outbreaks (outbreak 1: 27/74, 36.5%; outbreak 2: 17/24, 70.8%; outbreak 3: 11/13, 84.6%). Our results show that H. ducreyi was more frequently associated to skin lesions in the examined children than T. p. pertenue, but also that yaws is still present in Cameroon. These findings strongly advocate for a continuous effort to determine the aetiology of ulcerative skin lesions during these recurring outbreaks, and to inform the planned mass treatment campaigns to eliminate yaws in Cameroon.